University Studets’ Experience Of Pre-Service Studen-Teacher Teaching English Aboard: An Interview Study of A Student Exchange Program - Anisa Candra Rukmana; Angga Taufan Dayu; Raudatul Haura (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2021)
Educational institutions carry out several programs that are able to support the development of their students in preparation for becoming a teacher. Pre-service student teaching aboard is one of executable program. Through this international teaching, pre-service teachers got more dynamic experiences. Not to mention, the status of English in the country where they work is a second language. This research show the result regarding the challenges faced by student exchange participants while participating in pre-service teacher programs abroad and the impact of the experience they gained on their self-efficacy as future teacher candidates. there are so many challenges they have to face; starting from participating in the training provided by the faculty where they will be trained in their English language skills and monitored for their behavior for several days; find out about the school system and curriculum taught in the Philippines and then study it; looking for references on socio-cultural life to find out what can and cannot be done; adapting to the new school and living environment; language gap that makes their communication less fluent; different English terms; culture shock such as the striking attitude of some local people, speaking style; the weather is different from the country of origin. As well as the improvements they experienced after doing this program such as their confidence in their self-efficacy as teachers in the future.